Laboratory core investigations of sandstone-hosted uranium for in situ recovery. Issue 1 (2nd January 2020) - Zauner, Micha; Weller, Andreas; Halisch, Matthias
ABSTRACT: Several core plugs from a 1243 m-deep borehole penetrating the Westwater Canyon Member of the Morrison Formation in New Mexico (USA) have been investigated by various petrophysical methods to evaluate the potential of extracting deeply buried sandstone-hosted uranium deposits by in situ recovery (ISR). Petrophysics and mineralization patterns of the host rock in the target aquifer are crucial parameters for ISR amenability and were determined according to the ISR feasibility criteria. Mineralogical investigations revealed a secondary uranium mineralization mainly coating the silica grains of the arkosic sandstone and some interstitial pore fillings. The differences between mineralized and non-mineralized sandstone plugs are highlighted by nuclear magnetic resonance (NMR), X-ray microcomputed tomography, and spectral induced polarization (SIP). The NMR results show a doubling of the clay- and capillary-bound water and a decease of free-fluid porosity of mineralized samples. A correlation of mineralization grade and polarization is observed through the SIP investigations.